Risiko Finansial Teknologi Terhadap Green Finance di Indonesia - Edwin Basmar (POINT: Jurnal Ekonomi dan Manajemen, 2023)
The financial activity is an important part of green finance, but contra shock financial technology has a positive influence on the green finance growth in Indonesia. Based on the results by using Bank Indonesia data from 2019 to 2022 (time series) using the Ed Wave Index development model which combines the money quantity theory, finds that the relationship between technology financial risk and green finance is strongly influenced by the Velocity of Money, resulting in financial risk technology in the short term has a positive impact on green financial growth through the 3 wave points of the financial cycle in the economic growth area, this confirms that financial technology activities in the banking sector greatly support the green finance growth in Indonesia.